Measuring the Financial Performance of Indonesian Banking Industry Using Risk-Based Bank Rating - Cut Sjahrifa; Wiwiek Mardawiyah Daryanto; Vanya Kanyaka Ananggadipa (International Journal of Business Studies, 2018)
A bank has an important role in every country including Indonesia. The bank is aimed at maintaining economic growth and national financial stability. This study is to measure and analyze the financial performance between Bank Negara Indonesia (BNI), Bank Rakyat Indonesia (BRI), Bank Mandiri, and Bank Central Asia (BCA) against the national performance condition from under Bank Indonesia’s regulation No. 1 3 /1 /PBI/2 01 1 about Banks Financial Health Assessment. The data were collected from the annual report each company for the period 2012 – 2016. Furthermore, this study measure and analyze their level of financial health performance with Risk-based Bank Rating (RBBR) approach. RBBR examines NonPerforming Loan Ratio (NPL), Loan to Deposit Ratio (LDR), Current Account and Saving Account Ratio (CASA), Return on Asset (ROA), and Capital Adequacy Ratio (CAR). The result shows that those banks have a good financial performance which can be categorized into an ideal and very healthy condition. The finding results will be useful for students to deepen understanding about financial ratio and for bankers to analyze and make a strategy to improve the performance.